Sucrose consumption and dental health of twelve-year-old White, Coloured, Black and Indian children residing in the northern suburbs of Cape Town - Steyn, Nelia P.(Nelia Patricia) (Stellenbosch : Stellenbosch University, 2012)
Thesis (M. Sc.) -- University of Stellenbosch, 1983.